Maritime work low-carbon high-ductility cement-based material

By applying a combination design of low-carbon cementitious materials and high-ductility ECC materials in the field of offshore engineering, a low-carbon and high-ductility cement-based material in offshore engineering was prepared, which solved the problems of high carbon emissions, high cost and insufficient seawater erosion resistance in marine engineering, and achieved the low-carbon, ecological, high toughness and low-cost characteristics of the material.

CN119707407AActive Publication Date: 2025-03-28SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510039154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

When existing cement-based materials are used in the field of marine engineering, there are problems such as high carbon emissions, high cost, poor toughness and unsatisfactory resistance to seawater erosion.

Method used

A low-carbon cementitious material is used as the matrix and combined with the design concept of high-ductility ECC materials, a low-carbon and high-ductility cement-based material for offshore engineering is prepared by combining calcined clay, limestone powder, gypsum and some clinker. The composition of the material includes silicate cement, calcined clay, limestone powder, fly ash, river sand, gypsum, modified polyvinyl alcohol fibers and latex powder.

Benefits of technology

The material has excellent mechanical properties and seawater corrosion resistance, greatly reduced carbon emissions and reduced hydration heat release, reducing the risk of cracking in offshore structures during construction, and at the same time improving the ultimate stretching rate and flexural strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707407A_ABST
    Figure CN119707407A_ABST
Patent Text Reader

Abstract

The invention provides a maritime work low-carbon high-ductility cement-based material and a preparation method thereof. The maritime work low-carbon high-ductility cement-based material mainly comprises the following raw materials: Portland cement, calcined clay, limestone powder, fly ash, river sand, gypsum, a water reducing agent, modified polyvinyl alcohol fibers, latex powder and triethanolamine. The modified polyvinyl alcohol fiber is adopted, the calcined clay raw material is kaolin tailings, the kaolin tailings have high chemical activity and strong chloride ion binding capacity after being calcined, the cement-based material has the characteristic of low carbon due to utilization of a large proportion of solid waste, the latex powder can increase the binding force between the polymer fiber and a cement matrix, and the cement-based material can be used as a cement-based material. The fly ash is used as an auxiliary cementing material, so that the flowability of the composite material can be improved, and the green and low-carbon level of the base material can be further improved. After the raw materials are compounded, the cement-based material is high in coagulation efficiency and has good mechanical properties such as fracture resistance and compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement, and in particular to a marine engineering low-carbon high-ductility cement-based material. Background Art

[0002] As the most widely used building material at present, cement concrete also has an irreplaceable position in the process of ocean development. The performance requirements of marine engineering structures for cement-based materials are not just compressive strength. In many cases, they must also have excellent bending resistance, impact resistance and durability. This requires overcoming the problems of traditional cement concrete materials such as high heat generation, high brittleness, poor toughness, and easy cracking. At present, high-ductility cement-based materials (ECC) have been used in the repair and reinforcement of structural engineering, but their application in the field of marine engineering is not yet widespread. The important reason for this is that ECC materials are high in cost and carbon emissions, and their anti-corrosion performance in the marine environment has not been fully verified. The present invention provides a new type of cementitious material, which is obtained by compounding calcined clay, limestone powder, gypsum and part of the clinker, wherein the cement clinker is about 40% lower than that of ordinary Portland cement. Existing research results show that LC with a similar composition to the present invention 3 Cementitious materials have a denser microstructure and stronger chloride ion binding ability, and have a stronger ability to resist seawater erosion, but their flexural strength is low and their impact resistance is weak. If low-carbon cementitious materials are used as the matrix and combined with the design concept of high-ductility ECC materials, it is possible to create a low-carbon, ecological, high-toughness, low-cost marine low-carbon cement-based material. Patent CN116903334A discloses a low-carbon, low-shrinkage ECC material and a preparation method thereof. The patent uses a large proportion of calcined clay and limestone powder to replace cement. In parts by weight, ordinary silicate cement, calcined clay, limestone powder, quartz sand, PVA fiber, water, high-efficiency water reducer, and calcium sulfate whiskers are used to prepare LC 3 The material has a maximum direct tensile strain of only 2.6% after 28 days, and its crack control ability and tensile ductility are not high, and the durability of the material has not been measured. The patent CN117105595A discloses a low-carbon ECC material and a preparation method thereof, which uses a large amount of calcined clay and lightly burned dolomite powder to replace ordinary silicate cement, and contains the following raw material components: cement, calcined clay, lightly burned dolomite powder, quartz sand, PVA fiber, and high-efficiency water reducer. The technical solution does not record the relevant durability test results, and the formula contains dolomite powder with large composition fluctuations, which affects the stability of the ECC material to a certain extent. Summary of the invention

[0003] In view of this, the present invention proposes a marine low-carbon and high-ductility cement-based material to solve the above problems.

[0004] The technical solution of the present invention is achieved in this way:

[0005] A low-carbon and high-ductility cement-based material for marine engineering, characterized in that it is composed of the following components, measured by weight: 25-100 parts of silicate cement, 10-60 parts of calcined clay, 5-30 parts of limestone powder, 60-110 parts of fly ash, 55-100 parts of river sand, 1-3 parts of gypsum, 1-2 parts of water reducer, 2-3 parts of modified polyvinyl alcohol fiber, 0.5-1.0 parts of latex powder, 0.1-0.3 parts of triethanolamine, and 45-100 parts of water.

[0006] The preparation method of modified polyvinyl alcohol fiber comprises the following steps:

[0007] S1, modifying the surface of PVA fiber by spraying glue, mixing water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water, stirring, heating, heat preservation and homogenization, cooling to room temperature, and obtaining a primary glue solution;

[0008] S2, applying the primary glue solution to the PVA fiber to obtain a non-woven fabric, drying the non-woven fabric, hot rolling, adding a fixed shape, calendering, cooling, and winding to obtain a modified polyvinyl alcohol fiber.

[0009] Furthermore, the mass ratio of the water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water is 90-110:30-50:8-10:5-8:0.3-0.6:450-500; the epoxy-modified silicone oil is prepared by mixing vinyl cyclohexene oxide and low-hydrogen silicone oil with toluene as solvent and heating; the low-hydrogen silicone oil has an active hydrogen molar fraction of 0.06%-0.07% and a viscosity of 800-900mPa·s; the vinyl cyclohexene oxide and toluene are analytically pure; the heating is performed under nitrogen protection, the heating temperature is 80-85°C, and the time is 6-8h.

[0010] Furthermore, the alcoholysis degree of the water-soluble polyvinyl alcohol is 90%-99%, the polymerization degree is 1000-1500, the penetrant is one of penetrant JFC-1, penetrant JFC-2, and penetrant JFC-E, and the fineness of the modified polyvinyl alcohol fiber is 15-20tex.

[0011] Further, S1, the stirring rate is 200-220 rpm, the heating temperature is 95-100°C, and the heating time is 1.5-2h; the insulation homogenization temperature is 80-85°C, and the time is 1.0-1.5h; S2, the non-woven fabric preparation method is dry non-woven fabric preparation, the drying temperature is 40-55°C, the hot rolling temperature is 180-200°C, the spinning speed is 700-900m / min, the cooling method is annular blowing, the blowing temperature is 10-20°C, and the annular blowing speed is 0.2-10m / min.

[0012] Furthermore, the silicate cement is PI42.5 type silicate cement, and the mass proportion of its mineral components is: C2S accounts for 18%-25%, C3S accounts for 55%-60%, C4AF accounts for 8.5%-10%, and C3A accounts for 5.5%-8%. The initial setting time of the silicate cement is 115-125min, the final setting time is 180-190min, the 3d compressive strength is >17.0MPa, the 3d flexural strength is >3.5MPa, the 28d compressive strength is >42.5MPa, and the 28d flexural strength is >6.5MPa.

[0013] Furthermore, the calcined clay is obtained by calcining and grinding kaolin tailings at 750-800°C, with a particle size range of 0.1-30 microns and a specific surface area of ​​1.51-1.53m 2 / g. The limestone powder is heavy calcium stone powder with a particle size range of 0.3-30 microns and a specific surface area of ​​2.90-2.92m 2 / g, calcium carbonate content>95%.

[0014] Furthermore, the fly ash is secondary fly ash with a particle size range of 0.3-200 microns, the river sand particle size is 0.1-0.6 mm natural river sand, the gypsum is analytical pure dihydrate gypsum, and the water reducer is a polycarboxylate water reducer with a solid content of 18%-22% and a water reduction rate of 35%-40%.

[0015] Furthermore, the latex powder is a mixture of vinyl acetate and ethylene copolymer rubber powder in a mass ratio of 1:1.1-1.3, or a mixture of acrylic acid ester and styrene copolymer rubber powder in a mass ratio of 1:1.2-1.4.

[0016] A method for preparing a low-carbon and high-ductility cement-based material for marine engineering, characterized by comprising the following steps:

[0017] S1, mixing silicate cement, calcined clay, limestone powder and gypsum at a stirring speed of 90-100prm / min for 2-3min to obtain a mixed powder; adding fly ash and river sand to the mixed powder, mixing at a stirring speed of 90-100prm / min for 2-3min to obtain a mixture I;

[0018] S2, mixing the water reducer, triethanolamine and water, adding them to the mixture I at a uniform speed when the stirring speed is 90-100prm / min, stirring at a speed of 160-170prm / min, and stirring time of 2-3min to obtain mixture II;

[0019] S3, adding the modified polymer fiber and latex powder evenly to the mixture II at a stirring speed of 90-100prm, stirring at a stirring speed of 160-170prm / min for 2-3min to obtain a mixture III;

[0020] S4. Transfer the mixture III to the mold, vibrate for 1-2 minutes, smooth and shape it, and demold and cure it after 22-24 hours to obtain a high-ductility low-carbon cement-based material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The raw material of the calcined clay used in the present invention is kaolin tailings, which also contains a certain proportion of kaolin, which is a composite of silicon oxide and aluminum oxide. After high-temperature calcination, kaolin becomes metakaolin, which has higher chemical activity and stronger chloride ion binding ability. This makes the high-ductility low-carbon cement-based material of the present invention have excellent mechanical properties and seawater corrosion resistance.

[0023] (2) The present invention uses cementitious materials with a high amount of solid waste to prepare high-ductility cement-based materials for marine engineering, which has the characteristics of green and low carbon. The firing temperature of cement clinker is 1250°C, while the firing temperature of calcined clay is about 800°C, which greatly reduces the carbon emissions of marine engineering materials. The use of low-carbon cementitious materials to prepare high-ductility cement-based materials for marine engineering greatly reduces the hydration heat release of the material, which can effectively reduce the risk of cracking of marine structures during construction.

[0024] (3) The present invention uses redispersible latex powder and modified polyvinyl alcohol fiber to enhance the bonding force between the cement matrix and the fiber interface and improve the ultimate elongation of the fiber-reinforced composite material.

[0025] (4) The present invention uses a relatively high proportion of secondary fly ash as an auxiliary cementitious material, and can utilize its ball effect to improve the working performance of low-carbon cement-based material mixtures. In addition, the secondary fly ash used is a low-quality industrial solid waste with a wide source and low cost. It is used to prepare high-ductility cement-based materials, which can improve the carbon reduction and emission reduction level of low-carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Tensile stress diagram of Example 1. DETAILED DESCRIPTION

[0027] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0028] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0029] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0030] Low hydrogen silicone oil was purchased from Jinan Shanhai Chemical Technology Co., Ltd.; kaolin tailings came from Beihai Kaolin Technology Co., Ltd., and came from the fourth-level bottom slag solid waste produced by the fourth-level cyclone during the kaolin ore dressing process.

[0031] Preparation Example 1

[0032] The preparation method of modified polyvinyl alcohol fiber comprises the following steps:

[0033] S1, surface spraying modification of PVA fiber, mixing water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water in a mass ratio of 90:30:8:5:0.4:450, stirring at a stirring rate of 200 rpm, then heating at 100°C, keeping at 80°C for homogenization for 1.0h, and cooling to room temperature to obtain a primary glue solution;

[0034] The epoxy modified silicone oil is prepared by mixing vinyl cyclohexene oxide and low hydrogen silicone oil, using toluene as solvent, and heating. The active hydrogen mole fraction of the low hydrogen silicone oil is 0.06%, and the viscosity is 800 mPa·s. The purity of vinyl cyclohexene oxide and toluene is analytically pure. The heating is carried out under nitrogen protection, the heating temperature is 85°C, and the time is 8h.

[0035] The alcoholysis degree of the water-soluble polyvinyl alcohol is 90%, and the polymerization degree is 1000; the penetrant is the penetrant JFC-1, and the fineness of the modified polyvinyl alcohol fiber is 20tex.

[0036] S2, the primary glue solution is glued on the PVA fiber, the preparation method is dry non-woven fabric preparation, the spinning speed is 700m / min, the non-woven fabric is dried, the drying temperature is 55°C, hot rolling, the hot rolling temperature is 200°C, fixed, calendered, cooled, the cooling method is annular blowing, the blowing temperature is 10°C, and the annular blowing speed is 2m / min. Rolling, to obtain modified polyvinyl alcohol fiber.

[0037] Preparation Example 2

[0038] The preparation method of modified polyvinyl alcohol fiber comprises the following steps:

[0039] S1, surface spraying modification of PVA fiber, mixing water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water in a mass ratio of 110:50:10:8:0.6:500, stirring at a stirring rate of 220 rpm, then heating at 100°C, keeping at 85°C for homogenization for 1.5 hours, and cooling to room temperature to obtain a primary glue solution;

[0040] The epoxy-modified silicone oil is prepared by mixing vinyl cyclohexene oxide and low-hydrogen silicone oil with toluene as solvent by heating. The active hydrogen molar fraction of the low-hydrogen silicone oil is 0.07%, and the viscosity is 900 mPa·s. The vinyl cyclohexene oxide and toluene are analytically pure. The heating is carried out under nitrogen protection at a temperature of 85°C for 8 hours.

[0041] The alcoholysis degree of the water-soluble polyvinyl alcohol is 98%, and the polymerization degree is 1400; the penetrant is the penetrant JFC-2, and the fineness of the modified polyvinyl alcohol fiber is 20tex.

[0042] S2, the primary glue solution is glued on the PVA fiber, the preparation method is dry non-woven fabric preparation, the spinning speed is 900m / min, the non-woven fabric is dried, the drying temperature is 55°C, hot rolling, the hot rolling temperature is 200°C, fixed, calendered, cooled, the cooling method is annular blowing, the blowing temperature is 20°C, and the annular blowing speed is 9m / min. Rolling, to obtain modified polyvinyl alcohol fiber.

[0043] Preparation Example 3

[0044] The preparation method of modified polyvinyl alcohol fiber comprises the following steps:

[0045] S1. Surface spraying modification of PVA fiber was performed. Water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water were mixed and stirred in a mass ratio of 100:40:9:7:05:450 at a stirring rate of 210 rpm. The mixture was then heated at 95° C. and homogenized at 80° C. for 1.0 h. The mixture was cooled to room temperature to obtain a primary glue solution.

[0046] The epoxy modified silicone oil is prepared by mixing vinyl cyclohexene oxide and low hydrogen silicone oil, using toluene as solvent, and heating. The active hydrogen molar fraction of the low hydrogen silicone oil is 0.06%, and the viscosity is 800 mPa·s. The purity of vinyl cyclohexene oxide and toluene is analytically pure. The heating is carried out under nitrogen protection, the heating temperature is 80°C, and the time is 7 hours.

[0047] The alcoholysis degree of the water-soluble polyvinyl alcohol is 90-99%, and the polymerization degree is 1000-1500; the penetrant is the penetrant JFC-E, and the fineness of the modified polyvinyl alcohol fiber is 18 tex.

[0048] S2, applying the primary glue solution to the PVA fiber, the preparation method is dry non-woven fabric preparation, the spinning speed is 800m / min, the non-woven fabric is dried, the drying temperature is 50°C, hot rolling, the hot rolling temperature is 190°C, fixed, calendered, cooled, the cooling method is annular blowing, the blowing temperature is 15°C, and the annular blowing speed is 6m / min. Rolling, to obtain modified polyvinyl alcohol fiber.

[0049] Example 1

[0050] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0051] 50 parts of silicate cement, 32 parts of calcined clay, 16 parts of limestone powder, 60 parts of fly ash, 56 parts of river sand, 2 parts of gypsum, 1 part of water reducer, 3 parts of modified polyvinyl alcohol fiber prepared in Preparation Example 1, 1.0 part of latex powder, 0.2 parts of triethanolamine, and 48 parts of water.

[0052] Among them, the silicate cement is PI42.5 type silicate cement, and its mineral components account for 20% by mass of C2S, 55% of C3S, 9% of C4AF, and 6% of C3A. The density is 3.1g / cm 3 The initial setting time is 120 minutes and the final setting time is 180 minutes.

[0053] Among them, calcined clay is obtained by calcining and grinding kaolin tailings at 750-800℃, with a specific surface area of ​​1.52m 2 / g. The limestone powder is heavy calcium stone powder with a particle size range of 25 microns and a specific surface area of ​​2.9m 2 / g, calcium carbonate 98%.

[0054] Among them, the fly ash is secondary fly ash, with a particle size range of 150 microns and a specific surface area of ​​1.51m 2 / g; the river sand particle size is 0.4mm natural river sand; the gypsum is analytical pure dihydrate gypsum; the water reducer is polycarboxylic acid water reducer with a solid content of 20% and a water reduction rate of 35%.

[0055] The latex powder is a mixture of vinyl acetate and ethylene copolymer powder in a mass ratio of 1:1.1.

[0056] The production steps include:

[0057] Step (1): Mixing silicate cement, calcined clay, limestone powder and gypsum at a stirring speed of 100 prm / min for 3 min to obtain a mixed powder; adding fly ash and river sand to the mixed powder and mixing at a stirring speed of 100 prm / min for 3 min to obtain a mixture I;

[0058] Step (2): Mix the water reducer, triethanolamine and water, add them into the mixture I at a uniform speed at a stirring speed of 100prm / min, stir at a speed of 160prm / min, and stir for 3 minutes to obtain a mixture II;

[0059] Step (3): adding the modified polymer fiber and the latex powder evenly to the mixture II at a stirring speed of 100 rpm, stirring at a stirring speed of 160 rpm / min for 3 min to obtain a mixture III;

[0060] Step (4): Transfer the mixture III to a mold, vibrate for 2 minutes, smooth and shape it, and demold and cure it after 24 hours to obtain a high-ductility low-carbon cement-based material.

[0061] Example 2

[0062] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0063] 50 parts of silicate cement, 40 parts of calcined clay, 20 parts of limestone powder, 70 parts of fly ash, 60 parts of river sand, 2.5 parts of gypsum, 1.2 parts of water reducer, 2.5 parts of modified polyvinyl alcohol fiber prepared in Preparation Example 2, 0.8 parts of latex powder, 0.3 parts of triethanolamine, and 55 parts of water.

[0064] Among them, the silicate cement is PI42.5 type silicate cement, and its mineral components account for 23% by mass of C2S, 60% of C3S, 9% of C4AF, and 7% of C3A. The density is 3.2g / cm 3 The initial setting time is 125min and the final setting time is 190min.

[0065] Among them, calcined clay is obtained by calcining and grinding kaolin tailings at 750-800℃, with a particle size range of 15 microns and a specific surface area of ​​1.51m 2 / g. The limestone powder is heavy calcium stone powder with a particle size range of 18 microns and a specific surface area of ​​2.9m 2 / g, calcium carbonate content 96%.

[0066] Among them, the fly ash is secondary fly ash, with a particle size range of 100 microns and a specific surface area of ​​1.53m 2 / g; the river sand particle size is 0.3mm natural river sand; the gypsum is analytical pure dihydrate gypsum; the water reducer is polycarboxylic acid water reducer with a solid content of 22% and a water reduction rate of 40%.

[0067] The latex powder is a mixture of vinyl acetate and ethylene copolymer powder in a mass ratio of 1:1.2.

[0068] The production steps include:

[0069] Step (1): Mixing silicate cement, calcined clay, limestone powder and gypsum at a stirring speed of 95 prm / min for 3 min to obtain a mixed powder; adding fly ash and river sand to the mixed powder and mixing at a stirring speed of 95 prm / min for 2 min to obtain a mixture I;

[0070] Step (2): Mix the water reducer, triethanolamine and water, add the mixture into the mixture I at a uniform speed at a stirring speed of 95 prm / min, stir at a speed of 165 prm / min, and stir for 3 minutes to obtain the mixture II;

[0071] Step (3): adding the modified polymer fiber and the latex powder evenly to the mixture II at a stirring speed of 100 rpm, stirring at a stirring speed of 165 rpm / min for 3 min to obtain a mixture III;

[0072] Step (4): Transfer the mixture III to a mold, vibrate for 2 minutes, smooth and shape it, and demold and cure it after 24 hours to obtain a high-ductility low-carbon cement-based material.

[0073] Example 3

[0074] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0075] 50 parts of silicate cement, 35 parts of calcined clay, 12 parts of limestone powder, 55 parts of fly ash, 50 parts of river sand, 1.5 parts of gypsum, 1.3 parts of water reducer, 2.5 parts of modified polyvinyl alcohol fiber prepared in Preparation Example 3, 0.6 parts of latex powder, 0.2 parts of triethanolamine, and 60 parts of water.

[0076] Among them, the silicate cement is PI42.5 type silicate cement, and its mineral components account for 21% by mass of C2S, 57% of C3S, 8.5% of C4AF, 6% of C3A, and the density is 3.2g / cm 3 The initial setting time is 125min and the final setting time is 190min.

[0077] Among them, calcined clay is obtained by calcining and grinding kaolin tailings at 750℃, with a particle size range of 8 microns and a specific surface area of ​​1.53m 2 / g. The limestone powder is heavy calcium stone powder with a particle size range of 7 microns and a specific surface area of ​​2.91m 2 / g, calcium carbonate content 96%.

[0078] Among them, the fly ash is secondary fly ash, with a particle size range of 54 microns and a specific surface area of ​​1.53m 2 / g; the river sand particle size is 0.4mm natural river sand; the gypsum is analytical pure dihydrate gypsum; the water reducer is polycarboxylic acid water reducer with a solid content of 22% and a water reduction rate of 40%.

[0079] Among them, acrylic ester and styrene copolymer rubber powder are mixed in a mass ratio of 1:1.2.

[0080] The production steps include:

[0081] Step (1): Mixing silicate cement, calcined clay, limestone powder and gypsum at a stirring speed of 95 prm / min for 2 min to obtain a mixed powder; adding fly ash and river sand to the mixed powder and mixing at a stirring speed of 95 prm / min for 3 min to obtain a mixture I;

[0082] Step (2): Mix the water reducer, triethanolamine and water, add them into the mixture I at a uniform speed at a stirring speed of 100prm / min, stir at a speed of 170prm / min, and stir for 3 minutes to obtain a mixture II;

[0083] Step (3): adding the modified polymer fiber and the latex powder evenly to the mixture II at a stirring speed of 95 rpm, stirring at a stirring speed of 165 rpm / min for 2 min to obtain a mixture III;

[0084] Step (4): Transfer the mixture III to a mold, vibrate for 1.5 minutes, smooth and shape it, and demold and cure it after 23 hours to obtain a high-ductility low-carbon cement-based material.

[0085] Comparative Example 1

[0086] The difference between Comparative Example 1 and Example 1 is that "PI42.5 type silicate cement" is replaced by "PI32.5 type silicate cement". Other raw materials and preparation methods are the same as those of Example 1.

[0087] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0088] 50 parts of PI32.5 type silicate cement, 32 parts of calcined clay, 16 parts of limestone powder, 60 parts of fly ash, 56 parts of river sand, 2 parts of gypsum, 1 part of water reducer, 3 parts of modified polyvinyl alcohol fiber prepared in Preparation Example 1, 1.0 part of latex powder, 0.2 parts of triethanolamine, and 48 parts of water.

[0089] Among them, the manufacturer of PI32.5 type silicate cement is: Shandong Shan Aluminum Environmental New Materials Co., Ltd.

[0090] Comparative Example 2

[0091] The difference between Comparative Example 2 and Example 1 is that "50 parts of P1.42.5 type silicate cement" is replaced by "25 parts of PI32.5 type silicate cement, 25 parts of PI42.5 type silicate cement", and the raw material components latex powder and triethanolamine are removed. Other raw materials and preparation methods are the same as those in Example 1.

[0092] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0093] 50 parts of silicate cement, 32 parts of calcined clay, 16 parts of limestone powder, 60 parts of fly ash, 56 parts of river sand, 2 parts of gypsum, 1 part of water reducer, 3 parts of modified polyvinyl alcohol fiber prepared in Preparation Example 1, 1.0 part of latex powder, 0.2 parts of triethanolamine, and 48 parts of water.

[0094] The silicate cement includes 25 parts of PI32.5 silicate cement and 25 parts of PI42.5 silicate cement. The manufacturer of PI32.5 silicate cement is Shandong Shanlu Environmental New Materials Co., Ltd.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that the modified polyvinyl alcohol fiber is replaced by polyvinyl alcohol fiber (unmodified), the manufacturer of the polyvinyl alcohol fiber is Shandong Jinhongyao Engineering Materials Co., Ltd., and the other raw materials and production methods are the same as those in Example 1.

[0097] A high-ductility low-carbon cement-based material and a preparation method thereof, wherein the raw materials include the following parts by weight:

[0098] 50 parts of Portland cement, 32 parts of calcined clay, 16 parts of limestone powder, 60 parts of fly ash, 56 parts of river sand, 2 parts of gypsum, 1 part of water reducer, 3 parts of polyvinyl alcohol fiber, 1.0 part of latex powder, 0.2 parts of triethanolamine, and 48 parts of water.

[0099] test

[0100] The characterization methods and test specimen dimensions described in the following embodiments are as follows:

[0101] The uniaxial stress-strain curve was obtained by uniaxial tensile test. The test specimen was a dog-bone type specimen recommended by the Japan Society of Civil Engineers. The gauge area dimensions of the test specimen were 80 mm in length, 30 mm in width, and 13 mm in thickness.

[0102] The anti-ion penetration performance test was conducted using the electric flux method in the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GBT50082-2009). The test used a cylindrical specimen with a diameter of 100 mm and a height of 50 mm, and the electric flux values ​​at 28 days and 56 days were tested. The drying shrinkage strain test method refers to JC / T 603-2004 "Cement Mortar Drying Shrinkage Test Method", and the test specimen size is a prism of 25 mm × 25 mm × 280 mm. The mixer used in the present invention is a planetary mixer.

[0103] The compressive strength of the cement-based materials prepared by the methods of Examples 1-3 on the 7th and 28th days was higher than that of Comparative Examples 1-3, and the ultimate tensile strength and tensile strain capacity were improved. The silicate cement prepared by the methods of Examples 1-3 shortened the initial setting time and the final setting time, and at the same time, reduced the electrical flux on the 28th and 56th days, and improved the shrinkage values ​​on the 28th, 56th and 90th days (Tables 1 and 2).

[0104] Table 1

[0105]

[0106] Table 2

[0107] Components 28d shrinkage value 56d shrinkage value 90d shrinkage value Example 1 1238 1335 1393 Example 2 1254 1332 1381 Example 3 1244 1339 1398 Comparative Example 1 1180 1262 1275 Comparative Example 2 1106 1212 1228 Comparative Example 3 1138 1235 1293

[0108] Test results: The present invention uses silicate cement, calcined clay, limestone powder, fly ash, modified polyvinyl alcohol fiber, 0.6 parts of latex powder, triethanolamine and other raw materials in combination, wherein the raw materials for preparing the modified polyvinyl alcohol fiber include water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water, and performs hot rolling reinforcement and 2 times of gluing. The cement-based materials prepared according to the methods of Examples 1-3 of the present invention effectively improve the flexural strength and compressive strength. The compressive strength of the cement-based materials prepared by the methods of Examples 1-3 on the 7th and 28th days is higher than that of Comparative Examples 1-3, and its ultimate tensile strength and tensile strain capacity are improved, the setting time is shortened, the electric flux on the 28th and 56th days is reduced, and the shrinkage values ​​on the 28th, 56th and 90th days are increased. When the raw materials are changed in Comparative Examples 1-3, the flexural strength and compressive strength are reduced when ordinary silicate cement and ordinary polyvinyl alcohol fiber are changed, and the electric flux is increased. Therefore, the cement-based material prepared by the raw materials, raw material ratio and preparation method of the present invention has high coagulation efficiency and good application effects of anti-bending and anti-compression.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-carbon and high-ductility cement-based material for marine engineering, characterized in that: The invention is composed of the following components in parts by weight: 25-100 parts of silicate cement, 10-60 parts of calcined clay, 5-30 parts of limestone powder, 60-110 parts of fly ash, 55-100 parts of river sand, 1-3 parts of gypsum, 1-2 parts of water reducer, 2-3 parts of modified polyvinyl alcohol fiber, 0.5-1.0 parts of latex powder, 0.1-0.3 parts of triethanolamine, and 45-100 parts of water; The preparation method of modified polyvinyl alcohol fiber comprises the following steps: S1, modifying the surface of PVA fiber by spraying glue, mixing water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water, stirring, heating, heat preservation and homogenization, cooling to room temperature, and obtaining a primary glue solution; S2, applying the primary glue solution to the PVA fiber to obtain a non-woven fabric, drying the non-woven fabric, hot rolling, adding a fixed shape, calendering, cooling, and winding to obtain a modified polyvinyl alcohol fiber.

2. A marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The mass ratio of the water-soluble polyvinyl alcohol, diethylene glycol dibenzoate alum, epoxy-modified silicone oil, rubber powder, penetrant and water is 90-110:30-50:8-10:5-8:0.3-0.6:450-500.

3. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The epoxy modified silicone oil is prepared by mixing vinyl cyclohexene oxide and low hydrogen silicone oil, using toluene as solvent, and heating; the active hydrogen molar fraction of the low hydrogen silicone oil is 0.06%-0.07%, and the viscosity is 800-900mPa·s; the vinyl cyclohexene oxide and toluene are analytically pure; the heating is carried out under nitrogen protection, the heating temperature is 80-85°C, and the time is 6-8h.

4. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The alcoholysis degree of the water-soluble polyvinyl alcohol is 90%-99%, and the polymerization degree is 1000-1500. The penetrant is one of penetrant JFC-1, penetrant JFC-2, and penetrant JFC-E. The fineness of the modified polyvinyl alcohol fiber is 15-20 tex.

5. The marine low-carbon high-ductility cement-based material according to claim 2, characterized in that: S1, the stirring rate is 200-220 rpm, the heating temperature is 95-100°C, and the heating time is 1.5-2h; the heat preservation and homogenization temperature is 80-85°C, and the time is 1.0-1.5h; S2, the non-woven fabric preparation method is dry non-woven fabric preparation, the drying temperature is 40-55°C, the hot rolling temperature is 180-200°C, the spinning speed is 700-900m / min, the cooling method is annular blowing, the blowing temperature is 10-20°C, and the annular blowing speed is 0.2-10m / min.

6. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The silicate cement is PI42.5 type silicate cement, and its mineral components account for the following mass ratios: C2S accounts for 18%-25%, C3S accounts for 55%-60%, C4AF accounts for 8.5%-10%, and C3A accounts for 5.5%-8%. The initial setting time of the silicate cement is 115-125min, the final setting time is 180-190min, the 3d compressive strength is >17.0MPa, the 3d flexural strength is >3.5MPa, the 28d compressive strength is >42.5MPa, and the 28d flexural strength is >6.5MPa.

7. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The calcined clay is obtained by calcining and grinding kaolin tailings at 750-800°C, with a particle size range of 0.1-30 microns and a specific surface area of ​​1.51-1.53m 2 / g; the limestone powder is heavy calcium stone powder, with a particle size range of 0.3-30 microns and a specific surface area of ​​2.90-2.92m 2 / g, calcium carbonate content>95%.

8. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The fly ash is secondary fly ash with a particle size range of 0.3-200 microns, the river sand particle size is natural river sand of 0.1-0.6 mm, the gypsum is analytical pure dihydrate gypsum, and the water reducer is a polycarboxylate water reducer with a solid content of 18%-22% and a water reduction rate of 35%-40%.

9. The marine low-carbon high-ductility cement-based material according to claim 1, characterized in that: The latex powder is a mixture of vinyl acetate and ethylene copolymer rubber powder in a mass ratio of 1:1.1-1.3, or a mixture of acrylic acid ester and styrene copolymer rubber powder in a mass ratio of 1:1.2-1.

4.

10. The method for preparing a low-carbon and high-ductility cement-based material for marine engineering according to claim 1, characterized in that: The production steps include: S1, mixing silicate cement, calcined clay, limestone powder and gypsum at a stirring speed of 90-100prm / min for 2-3min to obtain a mixed powder; adding fly ash and river sand to the mixed powder, mixing at a stirring speed of 90-100prm / min for 2-3min to obtain a mixture I; S2, mixing the water reducer, triethanolamine and water, adding them to the mixture I at a uniform speed when the stirring speed is 90-100prm / min, stirring at a speed of 160-170prm / min, and stirring time of 2-3min to obtain mixture II; S3, adding the modified polymer fiber and latex powder evenly to the mixture II at a stirring speed of 90-100prm, stirring at a stirring speed of 160-170prm / min for 2-3min to obtain a mixture III; S4. Transfer the mixture III to the mold, vibrate for 1-2 minutes, smooth and shape it, and demold and cure it after 22-24 hours to obtain a high-ductility low-carbon cement-based material.

Citation Information

Patent Citations

  • Low-carbon low-shrinkage engineering cement-based composite material and preparation method thereof

    CN116903334A

  • High-rheological-property geopolymer mortar and preparation method thereof

    CN111704399A

  • Low-carbon engineering cement-based composite material and preparation method thereof

    CN117105595A

  • Reinforcing fiber, method for producing same, and elastomer product using reinforcing fiber

    CN118251527A

  • Low-carbon high-strength wading cement-based composite material as well as preparation method and application thereof

    CN119100709A